Radar Technology - Kouemou, Guy (IntechOpen, 2010)
In this book "Radar Technology", the chapters are divided into four main topic areas: Topic area 1: "Radar Systems" consists of chapters which treat whole radar systems, environment and target functional chain. Topic area 2: "Radar Applications" shows various applications of radar systems, including meteorological radars, ground penetrating radars and glaciology. Topic area 3: "Radar Functional Chain and Signal Processing" describes several aspects of the radar signal processing. From parameter extraction, target detection over tracking and classification technologies. Topic area 4: "Radar Subsystems and Components" consists of design technology of radar subsystem components like antenna design or waveform design.